Design and development of GPS/GSM based vehicle tracking and alert system for commercial inter-city buses - Fleischer, P.B.; Nelson, A.Y.; Sowah, R.A.; Bremang, A. (Proceedings of the 2012 IEEE 4th International Conference on Adaptive Science and Technology, ICAST 2012, 2012)
In this paper we proposed the design, development and deployment of GPS (Global Positioning System)/GSM (Global System for Mobile Communications) based Vehicle Tracking and Alert System which allows inter-city transport companies to track their vehicles in real-time and provides an alert system for reporting armed robbery and accident occurrences. © 2012 IEEE.
Keywords: alert system; fleet management system; onboard navigation system; real-time monitoring